2011
DOI: 10.1111/j.1365-2966.2011.18342.x
|View full text |Cite
|
Sign up to set email alerts
|

Cepheid investigations using the Kepler space telescope

Abstract: We report results of initial work done on selected candidate Cepheids to be observed with the Kepler space telescope. Prior to the launch 40 candidates were selected from previous surveys and databases. The analysis of the first 322 days of Kepler photometry, and recent ground-based follow-up multicolour photometry and spectroscopy allowed us to confirm that one of these stars, V1154 Cyg (KIC 7548061), is indeed a 4.9-d Cepheid. Using the phase lag method we show that this star pulsates in the fundamental mode… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 48 publications
0
17
0
1
Order By: Relevance
“…The first results based on the first four quarters of Kepler data were published by Szabó et al (2011) who found V1154 Cyg to be single periodic. The frequency analysis did not reveal any additional pulsation frequency while the period remained stable during the last 40 years.…”
Section: Introductionmentioning
confidence: 99%
“…The first results based on the first four quarters of Kepler data were published by Szabó et al (2011) who found V1154 Cyg to be single periodic. The frequency analysis did not reveal any additional pulsation frequency while the period remained stable during the last 40 years.…”
Section: Introductionmentioning
confidence: 99%
“…The G star KIC 7548061 (V1154 Cyg) is a known and well-studied Cepheid (e.g. Pigulski et al 2009) and is the subject of a dedicated paper based on Kepler data by Szabó et al (2011). Sixty-two stars are known to belong to multiple systems, including at least fourteen eclipsing binaries (EB; KIC 1432149, Hartman et al 2004;KIC 10206340, Malkov et al 2006; catalogues by Prša et al 2011;.…”
Section: Sample Stars In the Literaturementioning
confidence: 99%
“…Photometry was obtained from the images using SEXTRACTOR (Bertin & Arnouts 1996), and calibrated to the standard magnitudes using standard star observation from Landolt (2009). Further details about the telescopes, the CCDs and the reduction of the imaging data can be found in Szabó et al (2011) andNgeow (2012), who used the same instrumentation for monitoring the Cepheid V1154 Cyg located within the Kepler field of view ).…”
Section: Ground-based Colour Photometrymentioning
confidence: 99%